Aggressive Bone Metastatic Prostate Cancer With Periosteal Reaction in 18F-Choline PET/CT. (February 2021) - De Leiris, Nicolas; Ruggeri, Valentin; Riou, Laurent; Laramas, Mathieu; Djaileb, Loïc
Abstract : Abstract: Prostate cancer bone metastases usually appear as osteosclerotic lesions. However, atypical lesions have also been described. We report herein the case of a 65-year-old man treated since 2013 for prostate cancer with early bone metastases. This asymptomatic patient was referred for 18 F-choline PET/CT due to a major elevation of prostate-specific antigen to >1500 ng/mL. The results indicated multiple bone lesions, disseminated on the axial skeleton, girdles, and upper extremities of femurs. Interestingly, we described the development of an intensely hypermetabolic spiculated periosteal reaction, evidencing a rapidly progressive disease.